2014
DOI: 10.4238/2014.january.8.8
|View full text |Cite
|
Sign up to set email alerts
|

Identifying differentially expressed genes and pathways in two types of non-small cell lung cancer: adenocarcinoma and squamous cell carcinoma

Abstract: ABSTRACT. Non-small cell lung carcinoma, NSCLC, accounts for 80-85% of lung cancers. NSCLC can be mainly divided into two types: adenocarcinoma (ADC) and squamous cell carcinoma (SCC). The purpose of our study was to identify and differentiate the pathogenesis of ADC and SCC at the molecular level. The gene expression profiles of ADC and SCC were downloaded from Gene Expression Omnibus under accession No. GSE10245. Accordingly, differentially expressed genes (DEGs) were identified by the limma package in R lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…Using gene expression profiling techniques, prior studies also demonstrated that adenocarcinoma and squamous cell NSCLCs have different expression portfolios (2,14), which is in line with our observation that the association between TP53 mutations and increased VEGF-A transcripts appears specific for adenocarcinoma of the lung. It is conceivable that the improved outcome that was previously reported by our group (5) in bevacizumab-treated patients who harbored TP53 mutations versus wild-type TP53 is due to the association between TP53 mutations and higher VEGF-A, the target for bevacizumab.…”
Section: Resultssupporting
confidence: 77%
“…Using gene expression profiling techniques, prior studies also demonstrated that adenocarcinoma and squamous cell NSCLCs have different expression portfolios (2,14), which is in line with our observation that the association between TP53 mutations and increased VEGF-A transcripts appears specific for adenocarcinoma of the lung. It is conceivable that the improved outcome that was previously reported by our group (5) in bevacizumab-treated patients who harbored TP53 mutations versus wild-type TP53 is due to the association between TP53 mutations and higher VEGF-A, the target for bevacizumab.…”
Section: Resultssupporting
confidence: 77%
“…We noted that the significant enriched pathways found in Table 6 (late-stage) are also identified in the work by Liu et al [76]. Except oocyte meiosis, the other four pathways are involved in two NSCLC subtypes: adenocarcinoma and squamous cell carcinoma.…”
Section: Resultssupporting
confidence: 72%
“…In a more recent study, Liu and colleagues [38] defined a set of differentially expressed genes and 16 pathways for AC and SCC. The most significant genes participated in the following pathways: cell cycle ( GSK3B , ATR , SKP2 , CDK1 , CDK2 , SMC3 , PLK1 , CCND3 ), DNA replication ( RFC2 , PRIM2 , MCM4 , MCM5 ), spliceosome ( PRPF19 , SRSF2 , THOC4 ), p53 signaling ( CDK1 , CDK2 , GTSE1 , ATR ), adherent junction ( IGF1R , TGFBR2 , CTNND1 ), and tight junction ( CKD4 , CASK , MPP5 ).…”
Section: Discussionmentioning
confidence: 99%